Peran Pendidikan Kewarganegaraan Dalam Membangun Karakter Moral Pelajar Di Era Modern - Rusnita, Ayu Novidaniati; Rifai, Muhammad; Simanjuntak, Sri Susanti; Parhusip, Feby Adelia; Yunita, Sri (Konsorsium Dosen Sekolah Tinggi Agama Islam (STAI) Al-Yasini Pasuruan, 2024)
This research delves into the pivotal role of civic education in molding the moral character of students within the context of the modern era. By employing a descriptive literature review methodology, the study meticulously analyzes a range of theoretical sources to elucidate how rapid socio-cultural transformations and technological advancements are impacting students' moral development. The findings underscore the indispensability of civic education in fostering a robust moral character among students. It highlights how civic education nurtures a strong work ethic and imbues students with values such as patriotism and self-sacrifice, which are deemed essential for the collective well-being of the nation. In a world characterized by rapid and constant change, civic education stands out as a crucial element in equipping students not only with knowledge about their rights and responsibilities but also with the moral fortitude to act in the best interest of society. This educational approach aims to produce conscientious, informed, and morally grounded citizens capable of navigating the complexities of modern life while contributing positively to their communities and the nation as a whole. The study also suggests that integrating civic education effectively within the curriculum can mitigate the adverse effects of socio-cultural shifts and technological progressions, thereby ensuring that students develop into well-rounded individuals with a balanced perspective on their civic duties and moral obligations.